2010
DOI: 10.1016/j.neuron.2010.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Glutamate Transport Promotes Dopamine Storage and Glutamate Corelease In Vivo

Abstract: SUMMARY Dopamine neurons in the ventral tegmental area (VTA) play an important role in the motivational systems underlying drug addiction, and recent work has suggested that they also release the excitatory neurotransmitter glutamate. To assess a physiological role for glutamate corelease, we disrupted the expression of vesicular glutamate transporter 2 selectively in dopamine neurons. The conditional knockout abolishes glutamate release from midbrain dopamine neurons in culture and severely reduces their exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
440
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 375 publications
(482 citation statements)
references
References 78 publications
32
440
3
Order By: Relevance
“…A role for VGluT2 in vesicular DA filling in TH neurons has been proposed based on in vitro studies , and it has been suggested that lower levels of vesicular DA in knock-out mice depleted of VGluT2 in TH neurons might explain the attenuated locomotion induced by acute injections of cocaine or methamphetamine in these knock-out mice (Birgner et al, 2010;Hnasko et al, 2010). However, support for the coexistence of DA and VGLUT2 within the same synaptic terminal or within the same synaptic vesicle in vivo requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A role for VGluT2 in vesicular DA filling in TH neurons has been proposed based on in vitro studies , and it has been suggested that lower levels of vesicular DA in knock-out mice depleted of VGluT2 in TH neurons might explain the attenuated locomotion induced by acute injections of cocaine or methamphetamine in these knock-out mice (Birgner et al, 2010;Hnasko et al, 2010). However, support for the coexistence of DA and VGLUT2 within the same synaptic terminal or within the same synaptic vesicle in vivo requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons within the VTA are not identical in the synaptic input they receive, nor do they project to identical targets (Beier et al, 2015). In addition, VTA neurons may release more than just dopamine, often co-releasing glutamate and GABA simultaneously (Hnasko et al, 2010;Root et al, 2014;Tritsch and Sabatini, 2012), which complicates the characterization of post-synaptic effects. An additional hindrance in translating addiction research involves the necessity of comparing results across experiments that can vary dramatically by a multitude of factors, including the drug concentration, method of delivery (eg, experimenter administered vs self-administration), timecourse of drug access (eg, hours of access per day, number of days of access), and the consequent neuroadaptations that occur from repeated drug exposure.…”
Section: Neurocircuitry Involved In Reward and Reinforcement Of Abusementioning
confidence: 99%
“…1A). Excision of the second exon of the VGLUT2 gene in cells that express Cre generates a frameshift that disrupts VGLUT2 translation and function in cKO mice (11). cKO mice were born at the expected Mendelian ratios and showed no gross anatomical or behavioral defects, in distinct contrast to animals with a ubiquitous VGLUT2 deletion, which die neonatally from respiratory failure (26).…”
Section: Vglut2 Expressionmentioning
confidence: 99%
“…In glutamatergic neurons, glutamate is loaded into synaptic vesicles before its release into the synaptic cleft. This essential process is carried out by the VGLUTs, and inactivation of VGLUTs ablates glutamate release and neurotransmission (10)(11)(12)(13)(14)(15). Three distinct VGLUTs have been described, and anatomical studies have established that VGLUT1, 2, and 3 are expressed by largely nonoverlapping and functionally distinct populations of glutamatergic neurons in the nervous system (16).…”
mentioning
confidence: 99%